Medieval Ashkenaz papers in honour of Alfred Haverkamp presented at the 17th World Congress of Jewish Studies, Jerusalem 2017 - World Congress of Jewish Studies; Cluse, Christoph 1964-; Müller, Jörg R.; Haverkamp, Alfred 1937-2021 (Forschungen zur Geschichte der Juden Abhandlungen, 2021)
Cover -- Title Pages -- Table of Contents -- Editors' Note -- Israel Jacob Yuval: Foreword -- Johannes Heil: From Venosa to Mainz? Considerations on the Origins of Jewish Life North of the Alps -- Eveline Brugger: Soli duci hic casus reservabitur? The Practicalities of Ducal Rule over the Jews in Medieval Austria -- Birgit Wiedl: Von des vorgenanten meines ampts wegen. The Judenrichter-A Search for Clues -- Jörn Roland Christophersen: "Under the Crozier of Mainz": Special Conditions for a Mobile Elite? -- Michael Schlachter: Managing Vulnerability or Opting Out? Jews in Post-Black Death Ashkenaz -- Thilo Becker: … von siner kunst und artznye wegen: On the Migration and Special Status of Jewish Doctors in Ashkenaz around 1400 -- Johannes Deißler: Hanna of Goslar. A Jewess between the Goslar Town Council and the Counts of Regenstein -- Gerd Mentgen: The Ritual Murder Libel of Geisingen in the Year 1518 -- Jörg R. Müller: Michel Jud von Landau-A Jewish Military Leaderin the Late Thirteenth Century? -- Alessandra Veronese: Ashkenaz in Italy: German-Jewish Families in Cremona (First half of the Fifteenth Century) -- René Richtscheid: Christian and Jewish Kabbalists in the Moselle Region -- Christoph Cluse and Carsten Ginsheimer: A Twelfth-Century Life of Saint Matthias and its Jewish Source -- Elisheva Baumgarten: Local Knowledge: The Story of a Holy Robe -- Merav Schnitzer Maimon: Debating Fashion: Rabbinical Attitudes towards Medieval Bras -- Judith Olszowy-Schlanger: Jewish-Christian 'Notarial' Encounters The Scribes of the Hebrew Documents of Cologne and their Practices -- Andreas Lehnertz: Jewish Seals and Sealing Practices in the Medieval Holy Roman Empire: Authentication and Self-Representation -- Ephraim Kanarfogel: The Role of the Tosafists in Jewish-Christian Polemics.